1960
DOI: 10.1073/pnas.46.12.1533
|View full text |Cite
|
Sign up to set email alerts
|

The Loss of Phenotypic Traits by Differentiated Cells in Vitro, I. Dedifferentiation of Cartilage Cells

Abstract: The experiments to be described were designed to approach the following type of question: Will the differentiated state of a tissue cell survive multiple divisions in vitro? Do the cultured progeny of differentiated cells inherit the cellular mechanisms determining the unique somatic traits of their parental cells in a manner analogous to the way in which (1) Paramecia transmit Kappa particles to their daughter cells (Sonneborn,33 34 Beale,2 Preer3), (2) bacteria inherit genes for constitutive or inducible enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
168
1
6

Year Published

1980
1980
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 297 publications
(178 citation statements)
references
References 10 publications
3
168
1
6
Order By: Relevance
“…During the expansion phase, the cells dedifferentiate and gradually shift to a more fibroblastic phenotype, featured by a change in the synthesis of matrix constituents. 1,2 Generally, the dedifferentiation process is characterized by a downregulation of cartilage-specific proteoglycans and other cartilage structural proteins, such as collagen type II, cartilage oligomeric matrix protein, and collagen type IX. Concomitantly, the synthesis of matrix proteins characteristic of more fibrous tissues, such as collagen type I, are induced.…”
mentioning
confidence: 99%
“…During the expansion phase, the cells dedifferentiate and gradually shift to a more fibroblastic phenotype, featured by a change in the synthesis of matrix constituents. 1,2 Generally, the dedifferentiation process is characterized by a downregulation of cartilage-specific proteoglycans and other cartilage structural proteins, such as collagen type II, cartilage oligomeric matrix protein, and collagen type IX. Concomitantly, the synthesis of matrix proteins characteristic of more fibrous tissues, such as collagen type I, are induced.…”
mentioning
confidence: 99%
“…Studies that have examined the plasticity of the chondrocyte phenotype from many different species have consistently shown that culture of these cells in monolayers on plastic substrata for prolonged periods or upon repeated passages leads to the loss of their spherical shape and to the acquisition of an elongated fibroblast-like morphology (7,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). These morphologic alterations are accompanied by profound biochemical changes, including loss of the cartilage-specific phenotype, as evidenced by an arrest of the synthesis of the cartilage-specific collagens (types II, IX, and XI) and proteoglycans (aggrecan), initiation of synthesis of the interstitial collagens (types I, III, and V), and increase in the synthesis of fibroblasttype proteoglycans (versican) at the expense of aggrecan (7,17,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%
“…The long accepted postulation has been that low seeding densities allow for higher proliferation rates but lead to more pronounced de-differentiation (Holtzer et al 1960, Watt 1988. Several mechanisms have been suggested to explain this phenomenon, including more population doublings before confluence is reached and changes in cytoskeletal microfilament organization (Lim et al 2000, Mandl et al 2004.…”
Section: Discussionmentioning
confidence: 99%